(untitled) (International Journal of Medical and Surgical Sciences, 2016)
The goal of regenerative endodontics is to reinstate normal pulp function in traumatized, necrotic and infected teeth that would result in reestablishment of their functions, but still fail to re-establish real pulp tissue and give unpredictable results. The aim of this review was to compile and synthesize available information on the histological evidence of tissue pulp-dentinal complex formed through guided tissue regeneration. A web-based research on MEDLINE was done using filter terms Review, published in the last 10 years and Dental journals. Keywords used for research were “Pulp", "Dentin", "Regeneratión", "Tissue” and "Histologic". The search yielded about 140 articles; the interest were selected and downloaded in full text. The most encouraging studies regarding guided tissue regeneration have been described in case reports of immature teeth diagnosed with irreversible pulpitis in which the histology odontoblasts type cells were observed. However, there are no studies with long-term follow up on this type of therapy. Some treatment protocols might result in undesired and unpredictable outcomes. Efforts are required to improve and update existing regenerative endodontic strategies to make it an effective, safe, and biological mode to save teeth.